In vitro erythropoiesis at different pO2 induces adaptations that are independent of prior systemic exposure to hypoxia - Simionato, Greta; Rabe, Antonia; Gallego-Murillo, Joan Sebastián; van der Zwaan, Carmen; Hoogendijk, Arie Johan; van den Biggelaar, Maartje; Minetti, Giampaolo; Bogdanova, Anna; Mairbäurl, Heimo; Wagner, Christian; Kästner, Lars; van den Akker, Emile (Cells, 2022)
Hypoxia is associated with increased erythropoietin (EPO) release to drive erythropoiesis. At high altitude, EPO levels first increase and then decrease, although erythropoiesis remains elevated at a stable level. The roles of hypoxia and related EPO adjustments are not fully understood, which has contributed to the formulation of the theory of neocytolysis. We aimed to evaluate the role of oxygen exclusively on erythropoiesis, comparing in vitro erythroid differentiation performed at atmospheric oxygen, a lower oxygen concentration (three percent oxygen) and with cultures of erythroid precursors isolated from peripheral blood after a 19-day sojourn at high altitude (3450 m). Results highlight an accelerated erythroid maturation at low oxygen and more concave morphology of reticulocytes. No differences in deformability were observed in the formed reticulocytes in the tested conditions. Moreover, hematopoietic stem and progenitor cells isolated from blood affected by hypoxia at high altitude did not result in different erythroid development, suggesting no retention of a high-altitude signature but rather an immediate adaptation to oxygen concentration. This adaptation was observed during in vitro erythropoiesis at three percent oxygen by a significantly increased glycolytic metabolic profile. These hypoxia-induced effects on in vitro erythropoiesis fail to provide an intrinsic explanation of the concept of neocytolysis.
Im Text ist die Zahl 2 tiefgestellt
Gesehen am 18.05.2022